Scoping study of capacities and needs for strengthening water-energy-food-ecosystems (WEFE) NEXUS approaches with a gender and youth focus among public sector institutions in Uzbekistan - Namozov, Orifjan; Babajanova, Zukhra; Sin, Liliana; Djumanazarova, Aygul (2024)
This report of a Nexus Capacity Assessment provides a baseline understanding of the current capacity of relevant WEFE institutions and stakeholders to apply WEFE thinking and approaches. The key targeted stakeholders are the WEFE-related government ministries/departments and academic institutions, including women professionals within these institutions. A specific objective is to assess capacities and the enabling environment for the leadership of women and young professionals in Uzbekistan’s public WEFE institutions to develop fit-for-purpose capacity development programs for these groups.